Sustainability Assessment of the Palestinian Ready-Mixed Concrete Industry - Raee, Marah; Shami, Noor; Jadi, Hussam; Amer, Shatha (My University, 2021)
The ready- mix concrete industry is considered one of the strategic industries in all countries of the world, where the industry is of great importance in construction and reconstruction projects. This industry has a particular significance in Palestine specially in this particular time, where the Palestinian society is undergoing a phase of construction and reconstruction, which increases the demand for ready-mix concrete, where all construction works are based on this basic material, this industry plays a major role in supporting the local economy and the provision of many jobs directly and indirectly. However, this industry faces many challenges related to sustainable development, as it is one of the most resource-consuming industries, it also has considerable impact on the environment, resulting from the materials used in producing it. Also from the dust and emissions resulting from manufacturing and transportation processes. Sustainable manufacturing is one of the main concepts accompanying the emergence of sustainable development. It seeks to make the product take into consideration throughout its life cycle the dimensions of sustainable development. The principle of sustainable manufacturing is applied to production processes, products, and services through reducing the consumption of raw materials and energy, rationalizing water consumption, eliminating toxic emissions from manufacturing processes and reduces waste by treating, recycling and reusing it. This requires new technologies, it also requires increasing factory owners' awareness of the importance of applying sustainable development principles to ensure economic, social and environmental stability for future generations. This project aims to assess the current state of ready-mixed concrete plants in the northern West Bank. To achieve this goal, first we gathered enough information on the ready-mix concrete industry as well as the concept of sustainable development through literature reviews. Next step was established hypotheses for the study based on our knowledge of these principles. Based on the literature reviews and hypotheses, we developed an assessment tool with three parts: the first part included the factory's demographic data, the second part assessed the awareness of the concept of sustainability in these factories, and the third part evaluated the factory's sustainability practices from an environmental, economic, and social standpoint. The questionnaire has distributed to 27 ready-mixed concrete plants in the northern West Bank governorates. Then the collected data was analyzed using the SPSS analytical software. Last but not least, we came to several conclusions, the most important of which was that while ready-mixed concrete plants were very aware of the concept of sustainability and its practices, this did not reflect positively on the evaluation of practices, as we discovered a clear gap between the current system in ready-mixed concrete plants and the sustainability requirements, since many of plants managers’ believe that adopting new technologies and systems in the factory is financially costly and waste of time. In addition to the government's lack of control over the quantity of emissions from these plants and the degree of their influence on the surrounding environment. Finally, we suggested some recommendations that could contribute to the development of sustainability in this sector. However, despite the obvious gap between current circumstances and sustainability requirements, some sustainability philosophy requirements have been partially implemented, giving these plants a better evaluation in their application of sustainability philosophy and improving their chances of reaching advanced levels in this system.